Energy aspects of automobile transport development - Borodenko, Y.; Hnatov, A.; Arhun, S.; Sokhin, P.; Бороденко, Юрій Миколайович; Гнатов, Андрій Вікторович; Аргун, Щасяна Валіковна (Харківський національний автомобільно-дорожній університет, 2023)
Improving automobile transport means increasing fuel economy and environmental indicators. Fuel, in a broad sense, means energy used to activate the car's power plant. Potential energy is dispersed in the earth’s interior, on its surface, in the atmospheric air, and even in space. Moreover, some of them exist in different substances. On the one hand, the efficiency of an energy product use is assessed by its energy intensity; on the other hand, it is evaluated by the costs of its production (transportation) and the quality of its transformation into a consumer type of energy. Special attention is paid to renewable and unlimited kinds of energy sources. Goal. The purpose of the study is a qualitative analysis of the road transport development direction from the standpoint of the alternative energy sources use, taking into account the factors that comprehensively determine the economic and environmental indicators at the stages of production and processing of fossil raw materials, production of power plants and conversion, transformation, and transportation of energy in the field of transport technologies. Methodology. The first direction consists of the adaptation (conversion) of the design of thermal internal combustion engines for alternative liquid or gaseous fuel types. The advantage of this approach is minimal costs for engine conversion and fuel production. The second approach involves using hybrid power plants, consisting of a main and auxiliary engine, an energy source or accumulator, an energy converter, and a braking recuperation system. The third direction is the use of non-traditional energy sources. Results. The directions of the development of power plants for motor vehicles related to the increase in the energy density of hydrocarbon fuels, the use of hybrid power plants, and the use of alternative energy sources have been determined. A qualitative assessment of the considered approaches is given. Originality. A comprehensive approach to evaluating the effectiveness of using alternative types of energy in road transport is considered in terms of energy, economic, and environmental indicators. Practical value. The obtained results can be regarded as recommendations when drawing up plans for the evolution of industries of fossil extraction and transformation of other energy resources, the development of motor vehicles, and transport infrastructure technologies, taking into account the natural and industrial potential of the country.
Енергетичні аспекти розвитку автомобільного транспорту
Keywords: energy source; fuel energy density; alternative drives; hybrid power plant; traction battery; fuel cells; solar cells; cryogenic installations; road transport; джерело енергії; енергетична щільність палива; альтернативні приводи; гібридна силова установка; тягова батарея; паливні елементи; сонячні батареї; криогенні установки; автомобільний транспорт; 629.331; 10.30977/AT.2219-8342.2023.53.0.05